Penguatan Modal Sosial untuk Mewujudkan Keharmonisan Masyarakat Multikultural Kota Jayapura - Sahetapy, Aknes P (Program Doktor Ilmu Sosial Universitas Cenderawasih, 2025)
This research aims to understand how multicultural communities in Waena Village build social capital to overcome differences, tensions and create an inclusive and harmonious life. Diversity often triggers conflict, tension and mutual distrust, both among the community and elites who prioritise personal or group interests. This research focuses on how communities construct social capital to support social integrity. This research uses a descriptive qualitative approach with a constructivistic paradigm. This paradigm recognises that social reality is formed from individual constructions based on their experiences and social environment, so that each individual has a different perception of a phenomenon. Data collection techniques included in-depth interviews, participatory observation, and documentation studies. Data analysis was done thematically by identifying patterns of social big77 interaction, values upheld, and participation practices in the community. The results showed that the diversity of multicultural communities is a potential to strengthen social relations through trust, social networks, and norms that become social control. This social capital is supported by active community participation and inclusive leadership. These elements become the foundation of social interaction that unites diversity, creating integrity, solidarity and harmony in community life. Social capital plays an important role in managing differences in a multicultural society. With strong trust, social relations and norms, communities can overcome potential conflicts and build more inclusive and harmonious lives.